2019
DOI: 10.1177/0885066619828959
|View full text |Cite
|
Sign up to set email alerts
|

Current Use and Impact on 30-Day Mortality of Pulmonary Artery Catheter in Cardiogenic Shock Patients: Results From the CardShock Study

Abstract: Background: Cardiogenic shock (CS) is the most life-threatening manifestation of acute heart failure. Its complexity and high in-hospital mortality may justify the need for invasive monitoring with a pulmonary artery catheter (PAC). Methods: Patients with CS included in the CardShock Study, an observational, prospective, multicenter, European registry, were analyzed, aiming to describe the real-world use of PAC, evaluate its impact on 30-day mortality, and the ability of different hemodynamic parameters to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 28 publications
2
45
0
2
Order By: Relevance
“…43,44 Rossello et al 16 showed the use of PAC to be associated with lower mortality in CS from non-AMI aetiology, but no differences in those with AMI-CS. In a subgroup analysis of the CardShock study, Sionis et al 17 noted the use of a PAC to be associated with greater use of aggressive therapies (including inotropes) but without any differences in in-hospital mortality. This study noted a declining trend in the use of PAC in AMI-CS, which is in contrast to similar studies from patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Rossello et al 16 showed the use of PAC to be associated with lower mortality in CS from non-AMI aetiology, but no differences in those with AMI-CS. In a subgroup analysis of the CardShock study, Sionis et al 17 noted the use of a PAC to be associated with greater use of aggressive therapies (including inotropes) but without any differences in in-hospital mortality. This study noted a declining trend in the use of PAC in AMI-CS, which is in contrast to similar studies from patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The product of these combined parameters is the cardiac power (CP), and is the strongest haemodynamic predictor of mortality in the SHOCK trial registry [7]. This finding was confirmed in a more recent study, where the cardiac power index (CPI) was found to be the best haemodynamic predictor of survival in a CS population [8].…”
Section: Introductionmentioning
confidence: 69%
“…When comparing the different Impella devices, the Impella 2.5 in general achieves a lower performance relative to the Impella 5.0 in both CP (+48% vs +82%) and CPI (+58% vs +102%). The observed increase in CP(I) during Impella support, which has been shown to be a strong haemodynamic predictor of survival in CS [7,8], should theoretically lead to a reduction in mortality. Extrapolating from the survival graph of Fincke et al, the increase of CP from 0.5 W to 0.9 W should decrease mortality from approximately 50% to 20% [7].…”
Section: Discussionmentioning
confidence: 92%
“…Remarkably, RHC was used intentionally to optimize pharmacological treatment, not only for those that did not prove any benefit; additionally, it was associated with a higher risk of adverse events, predominantly PAC infection [85]. Sionis [86] and co-workers analyzed the data of cardiogenic shock (CS) patients included in the CardShock registry. Eighty-two of them (37.4%) diagnosed with PAC received goal-oriented therapy consisting of mechanical ventilation, renal replacement therapy, and mechanical assist devices more often as compared to the routinely assessed group of patients ( p < 0.01).…”
Section: Clinical Practice Implicationsmentioning
confidence: 99%